Total Quality Management, Balanced Scorecard and Performance - Mahfud Sholihin; Ayu Chairina Laksmi (Jurnal Akuntansi dan Auditing Indonesia, 2009)
This study examines the relationship between Total Quality Management (TQM), Bal-anced Scorecard (BSC), and organizational performance. In particular, this study investigates whether TQM affects performance; and if so, whether the effect is influenced by BSC implementa-tion. In examining the relationship between TQM, BSC and performance, this study proposes two different models, namely intervening/mediating model and moerating model. This study employs the intervening model to test whether the effect of TQM on performance is mediated by BSC. On the other hand, this study uses the moderating model to examine whether BSC moderates the re-lationship between TQM and performance. The results of this study demonstrate that both TQM and BSC are positively and significantly associated with performance. The path analysis reveals that partially, BSC mediates the relationship between TQM and performance. The results of mod-erated regression analysis, however, indicate there is no moderating effect of BSC on the rela-tionship between TQM and performance. Thus, the results of this study provide support for the in-tervening model, but not for the moderating model. The results, however, should be interpreted cautiously due to the limitations contained in this study.Keywords: Balanced Scorecard, Total Quality Management, performance